Measurement of Base-of-Support gait parameter using UWB radios - Chow, Justina Xiu Ting. (2013)
Gait analysis is the study of humans’ movements which in this report, focuses only on walking. This helps to identify early any abnormal gait which may be due to health problems. Observational gait analysis is the main way for therapist to record the patient’s walking pattern but it may not be accurate. With technology advancement, gait analysis can be more reliable with specialized equipment. Many accurate gait analysis had to be conducted in special laboratories and require specialist to operate the machines which is inconvenient for them. A technology with is more convenient for the patients to conduct gait analysis is to use wearable tracking systems. Ultra-wideband (UWB) is a new technology which may be accurate and reliable for patients to conduct their gait analysis as they are wearable and low cost. The objectives of this project is to prove the reliability of the UWB system compared to other tracking devices like the motion sensor and conduct an experiment to find the Base-of-Support (BOS) distance for different walking speeds.